Significantly improving the solubility and anti-inflammatory activity of fenofibric acid with native and methyl-substituted beta-cyclodextrins via complexation - Rajaram Rajamohan; Perumal Muthuraja; Kuppusamy Murugavel; Murali Krishnan Mani; D. S. Prabakaran; Jeong Hyun Seo; Tabarak Malik; Yong Rok Lee (Scientific Reports)
Abstract The solubility of commonly used anti-inflammatory drugs has become a significant concern in contemporary medicine. Furthermore, inflammatory arthritis stands out as the most prevalent chronic inflammatory disease globally. The disease’s pathology is characterized by heightened inflammation and oxidative stress, culminating in chronic pain and the loss of joint functionality. Fenofibric acid (FFA) exhibits notable anti-inflammatory potential. This research assesses the anti-inflammatory effects of FFA, both in its standalone form and as inclusion complexes (ICs) with β-cyclodextrin and its methyl derivatives. FFA is encapsulated within the cavities of cyclodextrins (CDs), a fact confirmed by spectral changes observed in FFA. Distinct rock and seed-like morphologies are apparent for FFA with CDs, indicating that the CDs have influenced the surface of the guest. The introduction of CDs significantly enhances the thermal stability of FFA. ICs demonstrate superior results in inflammation activity compared to FFA alone. The efficacy of FFA complexed with CDs in mitigating inflammation positions it as a promising new drug. Additionally, our findings reveal that incorporating FFA into the CD cavity as a drug release system enhances the pharmacological profile of this substance, FFA.